Pengaruh Penerapan PQ4R Terhadap Hasil Belajar Biologi Siswa Kelas X SMA Negeri 1 Mojolaban Tahun Pelajaran 2012/2013 - Istiqomah Wahyu Pradana; Slamet Santosa; Marjono Marjono (BIO-PEDAGOGI, 2013)
- The aim of this research is to know the influence of PQ4R strategy toward biology learning achievement of X degree students at SMA Negeri 1 Mojolaban in 2012/ 2013 academic year. This research was quasi experiment research which used posttest only Nonequivalent control group design. This research applyed PQ4R strategy in experimental group and deduktif approach with discussion, classical course and question-answer method in control group. Population’s research is the entire class X at SMA Negeri 1 Mojolaban in academic year 2012/2013.  Sampling techniques used cluster sampling. Cluster result has chosen X5 as experiment group and X7 as control group.  Data was collected using  multiple choice test, observation sheet, and document. The data were analyzed by t-test. This research concluded that application of PQ4R strategy has taken good effect toward student’s achievement cognitive, psychomotor, and affective domain in learning biology of SMA Negeri 1 Mojolaban. Key Words: PQ4R strategy,  Biology Learning Achievement